The Effectiveness of the Active Cycle of Breathing Technique and Peppermint Aroma Therapy on Reducing Shortness of Breath in Pulmonary Tuberculosis Patients at Sidikalang Regional General Hospital, Dairi Regency - Jojor Silaban; Perak Maruli Asi Roha Hutagalung; Tiur Romatua Sitohang; Risdiana Naibaho (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Tuberculosis (TB) has been a health problem in Indonesia and many countries, and it is included in Goal 3 of the Sustainable Development Goals (SDGs). Breathing pattern disorders caused by TB are a major problem that can lead to complications. This study aims to analyze the effectiveness of Active Cycle Breathing Technique (ACBT) and peppermint aromatherapy on reducing shortness of breath in patients with Pulmonary TB. The study was carried out in the Sidikalang Regional Hospital Polyclinic in patients with pulmonary TB. This study used a quasi-experimental design with a pre-post test. The number of samples in each case and control group was 35 people. Data analysis used the independent T-test at a significance level of 95% (α = 0.05). The results of the independent T-test showed a significance 0,008 (<0.05), which means that ACBT and peppermint aromatherapy are effective in reducing the scale of shortness of breath in Pulmonary TB patients at Sidikalang Regional Hospital. This study reveals that ACBT and peppermint aromatherapy can be integrated into clinical guidelines for the management of patients with respiratory disorders. The findings suggest that ACBT combined with peppermint aromatherapy may serve as an alternative therapy for alleviating shortness of breath. This procedure is relatively easy and inexpensive to perform and can be done independently at home without supervision. Keywords: ACBT, Peppermint aromatherapy, Shortness of breath, Pulmonary TB.